A Destructive Parenthood : The Problematic Motherhood in Selected Poems by Salvia Plath: Fatin Kaleel Ismael (Journal of the College of Education for Women, 2019)
A Destructive Parenthood : The Problematic Motherhood in Selected Poems by Salvia Plath